2019
DOI: 10.9740/mhc.2019.11.383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bexar County community pharmacist attitudes toward harm reduction

Abstract: Introduction Harm reduction is a term for strategies that minimize the negative outcomes of drug use. Given the progressing opioid epidemic, identifying barriers to harm reduction dispensing in community pharmacies is essential. Methods This online, survey-based study assessed community pharmacist attitudes toward harm reduction and perceived dispense rates of both naloxone and needles/syringes to patients without verifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Previous studies have indicated that non-opioid users hold overall positive opinions of naloxone. [12][13][14] A survey of lay persons found that while only 61% of respondents had heard of naloxone, most respondents (88%) felt naloxone was beneficial in preventing accidental opioid overdoses. 12 Both medical professionals and state government agencies support efforts to increase naloxone availability due to demonstrated benefits in reducing opioid overdose mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that non-opioid users hold overall positive opinions of naloxone. [12][13][14] A survey of lay persons found that while only 61% of respondents had heard of naloxone, most respondents (88%) felt naloxone was beneficial in preventing accidental opioid overdoses. 12 Both medical professionals and state government agencies support efforts to increase naloxone availability due to demonstrated benefits in reducing opioid overdose mortality.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Laws to permit pharmacistfacilitated naloxone provision quickly disseminated across all states and the District of Columbia from 2015 to 2018, and permission to sell nonprescription syringes at community pharmacies exist in all but 14 states presently. 9 However, the attitudes and behaviors of pharmacists and other pharmacy staff, [10][11][12][13][14][15][16][17] stigma and discrimination against people who use drugs during pharmacy interactions, 18,19 and structural factors like stocking of medications [20][21][22][23][24][25] have been identified as key barriers to the dispensing or sale of naloxone, buprenorphine, and nonprescription syringes in pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…, 46. , 47 , 48 , 49 , 50 Community pharmacist engagement in secondary and tertiary prevention efforts for HIV/HCV has been investigated to a lesser extent, often in approaches combining screening and referral to infectious disease treatment. 51 , 52 Across all levels of HIV/HCV prevention literature, variations in pharmacists' attitudes and beliefs, perceived barriers, and engagement in services emerge.…”
Section: Introductionmentioning
confidence: 99%